Analytical procedures for the audit of the competitiveness of trade enterprises - BARABASH, Nataliia; RIPA, Tetiana (Ius Modernum, 2018)
The article grounds the necessity to assess the level of competitiveness. The place and role of analytical procedures in the audit of the competitiveness of trade enterprise, as well as the specifics of their application at all stages of the audit, are investigated. The main methodological approaches to the application of such analytical procedures as «estimation of the financial condition of the trade enterprise», «assessment of the competitive position of the trading enterprise in the commodity market»and «assessment of the competitiveness of the trading enterprise»are presented.